Nghiên cứu quy trình tổng hợp dietylferrocen - Nam, Phạm Duy; Trường, Vương Văn; Thùy Trang, Đỗ Thị; Quỳnh Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Diethyl ferrocene is an important additive used in producing missile fuel. It plays role as a combustive catalyst in fuel component, it can enhance combustive rate of fuel from 2 to 3 times when its content is used from 1.5 to 2.5 wt%. In this paper, we report some results in synthesizing diethyl ferrocene. Its structure was confirmed by IR, 1H-, 13C-NMR and MS spectra. Its specifications were also investigated. Keywords: Diethyl ferrocene, ethylcyclopentadiene.